The integration of minorities in the security forces in Israel: the case of Muslim Arab citizens in the Galilee - Abu Ismail-Hassan, Kamleh (Kultura-Społeczeństwo-Edukacja, 2020)
Although many changes have occurred and accumulated significantly in Arab society in Israel and in the majority-minority relationship, the great class gap between Arabs and Jewish has been retained. This gap depends on the division of the resources in Israeli society. Inequality in this division and in the social relations between Jewish and Arabs continues, although there are indications that it is lessening. It is difficult to speak about co-existence and peace between Jews and Arabs, since today the Arabs of Israel are integrated in Israeli society primarily by negative and involuntary forces, such as economic dependency, political heresy, and social ecological isolation (Smooha, 2011: 13). The present research focuses only on the Muslim Arab population integrated into the security forces in Israel.